Day-Case Admission for External Dacryocystorhinostomy in Preschool Children. Issue 1 (January 2021) - Juniat, Valerie; Rose, Geoffrey E.; Timlin, H.; Wagh, V.J.; Abou-Rayyah, Y.; Uddin, J.; Verity, David H.
Abstract : Purpose: Epistaxis during or after dacryocystorhinostomy may present a risk of circulatory compromise, particularly in young children. In view of this concern, we reviewed the outcome and complications of external dacryocystorhinostomy in preschool children, aged less than 4½ years. Design: Retrospective noncomparative series. Patients and Methods: A case-note review for a series of preschool children undergoing external dacryocystorhinostomy as a day-case admission at Moorfields Eye Hospital between 1992 and 2018; all surgery was consultant-led. Details were taken of the type of surgery, any intraoperative or postoperative complications (surgical or anesthetic), any unplanned admissions after surgery, and the functional outcome. To assess the veracity of the medical records, the parents for a sample of 67 children were contacted to check whether there had been any unrecorded events or concerns. Outcome Measures: Anesthetic or surgical complications, unplanned admissions, and postoperative events. Results: One-hundred and eighty-seven children (117 boys; 63%) underwent 228 external dacryocystorhinostomies during 201 admissions, the average admission age being 36.8 months (median, 37.5; range, 5.5–53.5 months). Forty-one children (20%) underwent bilateral dacryocystorhinostomy: the 27 having simultaneous bilateral surgery dacryocystorhinostomy were operated at a mean age of 38.2 months (median, 37.5; range, 15.5–53.5 months), this being significantly different from the average age at first operation in 14 children undergoing sequential admission for bilateral dacryocystorhinostomy (mean, 24.9 months; median, 27.0; range, 5.5–42.5) ( p = 0.0023). No adverse anesthetic events were recorded, 2 children (2 dacryocystorhinostomies) required temporary nasal packing at the end of surgery for epistaxis, and one further child was admitted for overnight observation because of persistent mild epistaxis after bilateral dacryocystorhinostomy. Three children (3 dacryocystorhinostomies) had a mild, self-limiting secondary epistaxis, and there were no unplanned emergency admissions. The telephone survey did not reveal any disparity in the medical records. Conclusion: With experienced surgeons and anesthetists in a suitable specialist hospital, external dacryocystorhinostomy in preschool children would appear to be a safe and effective procedure, with few and minor complications. Although facilities for overnight observation should be available, the surgery can typically be planned as a day-case admission, and simultaneous bilateral surgery is also possible in this age-group. Abstract : External dacryocystorhinostomy (including simultaneous bilateral surgery) in preschool children aged < 4½ years appears to be safe when performed in a stand-alone eye hospital, and hemorrhagic circulatory compromise did not occur in 228 such cases.